Organizational And Economic Mechanisms Of Tourism Development - Botir Rahmatullayevich Pardayev (Periodica Journal, 2025)
The article examines the organizational and economic mechanisms of tourism development. As a result of researching different views, definitions of economic mechanisms and organizational-economic mechanisms in the field of tourism have been developed. The article also elaborates the classification and groups of organizational-economic mechanisms (TEM) in the tourism sector
Keywords: Tourism; integration; globalization